Does Neutrophil Gelatinase-Asociated Lipocalin Have Prognostic Value in Patients with Stable Angina Undergoing Elective PCI? A 3-Year Follow-Up Study - Hanna Bachorzewska-Gajewska; Anna Tomaszuk-Kazberuk; Iwona Jarocka; Elzbieta Mlodawska; Paulina Lopatowska; Malgorzata Zalewska-Adamiec; Slawomir Dobrzycki; Wlodzimierz J. Musial; Jolanta Malyszko (Karger Publishers, 2013)
Background: Neutrophil gelatinase-associated lipocalin (NGAL), a widely accepted diagnostic marker of acute renal injury (AKI) may be involved in the development of atherosclerosis. Purpose: To assess the prognostic significance of serum and urinary NGAL and serum cystatin C in patients with stable angina undergoing percutaneous coronary intervention (PCI) on a 3-year follow-up. Methods: We included patients with stable angina undergoing PCI. Serum NGAL and cystatin C were evaluated before and 4h, 8h after PCI. Urinary NGAL was evaluated before and 12h and 24h after the procedure. The primary end-point was all-cause mortality on a 3-year follow-up. Results: Among 132 patients there were 63% of males (mean age 64,5±9,8 years). Mean eGFR was 86.2±28.5 ml/min. During follow-up 8% of the patients died. All-cause mortality was significantly higher in patients with increased urinary NGAL concentration 12h after PCI (p=0.04). Urinary NGAL 12h after PCI correlated with eGFR (pConclusions: Increased urinary NGAL concentration is a strong predictor of mortality in patients with stable angina who undergo PCI and may be used for the risk stratification in this population.